2021
DOI: 10.1021/acs.est.1c01575
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight Inactivation of Human Norovirus and Bacteriophage MS2 Using a Genome-Wide PCR-Based Approach and Enzyme Pretreatment

Abstract: Human norovirus (hNoV) is an important etiology of gastrointestinal illness and can be transmitted via ingestion of contaminated water. Currently impractical to culture, hNoV detection is reliant on real-time polymerase chain reaction (RT-PCR)-based methods. This approach cannot distinguish between infective and inactivated viruses because intact regions of the RNA genome can amplify even if the damage is present in other regions of the genome or because intact genetic material is not contained within an infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 57 publications
6
23
0
Order By: Relevance
“…Eq was previously applied to virion inactivation by UV 254 , , and the discrepancy between genome-wide damage extrapolation and MS2 infectivity results by La-coated ceramic materials suggested that the MS2 inactivation process might be different from UV 254 inactivation. For example, the single-hit assumption might be not valid in which the damage of a single amplicon alone may not lead to the complete loss of virion infectivity, and the genome damage might not be random but targeted at specific bases or regions …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eq was previously applied to virion inactivation by UV 254 , , and the discrepancy between genome-wide damage extrapolation and MS2 infectivity results by La-coated ceramic materials suggested that the MS2 inactivation process might be different from UV 254 inactivation. For example, the single-hit assumption might be not valid in which the damage of a single amplicon alone may not lead to the complete loss of virion infectivity, and the genome damage might not be random but targeted at specific bases or regions …”
Section: Resultsmentioning
confidence: 99%
“…Individual amplicon damage was extrapolated to estimate genome-wide damage by combining the RT-qPCR amplification results from six amplicon assays. The proportion of fully intact genomes can be predicted by combining results from amplicons as eq 2: 37,38 Ä…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…RT-qPCR was performed for one genome target for MS2 and one target for Phi6, with targets described in Loeb et al 31 and Ye et al 32 (Table 1), respectively, using a Step-OnePlus TM real-time PCR system. Target size and base pair composition is described in the supplemental materials.…”
Section: Methodsmentioning
confidence: 99%